Effets de l'incorporation de fourrage de luzerne verte dans la ration alimentaire sur la qualité physico- chimique et microbiologique du lait, et sur l’aptitude fromagère des bactéries lactiques chez la brebis - ZAAF, Sabria Djanet (My University, 2022)
In Algeria, sheep’s milk, despite its importance for the dairy industry, remains a relatively less consumed product and less processed locally. The general objective of the work presented in this master’s thesis was to establish the relationship between the diet and the composition of sheep’s milk in order to evaluate the physicochemical and microbiological quality of raw sheep’s milk (Ouled Djellal breed) in western Algeria. This is done to constitute a reference on the contaminating flora of sheep milk in western Algeria.Physicochemical analysis of sheep’s milk collected from the Mostaganem farm «Hassi-Mameche», reveals a fat, protein, lactose, S.N.F and mineral content varying from (5.3-52.9%), (33-38%), (47-55.6g/l), (106.7-124.g/l), (6.6-8.9g/l) for sheep M1 (control) and (7.5-51.3%),(35-39.5%),(44.6-64g/l),(116.4-128.3g/l),(6.9-9.1g/l) for ewes M2 (experimental) respectively. the composition of the milk examined is rich compared to that of the bovine milk. Microbiological analyses indicate the presence of lactic bacteria identified by the genera Lactococcus, Leuconostoc, Lactobacillus, Enterococci, and Pediococcus. In a second study, two sheep breeds (Ouled Djellal and Taâdmit) were used to make a fresh cheese which gave very comfortable results regarding cheese yield (67g/100 ml) and ( 65g/100 ml) for Ouled Djellal and Taradmit respectively.
Keywords: diet; sheep’s milk; Ouled Djellal breed; physicochemical analysis